Đề bài:
Cho hai hàm số $f(x) = x^5 + 3x^3 – x^2 + 6x – 7$ và $g(x) = x^2 – 3$. Gọi $x_1,\, x_2, \,x_3,\, x_4, x_5$ là 5 nghiệm của phương trình $f(x) = 0$.
 
Hãy tính $P = g(x_1).g(x_2).g(x_3).g(x_4).g(x_5)$
Giải
\(\begin{array}{l} f\left( x \right) = \left( {x – {x_1}} \right)…\left( {x – {x_5}} \right)\\ g\left( {{x_1}} \right).g\left( {{x_2}} \right)….g\left( {{x_5}} \right) = \left( {{x_1} – \sqrt 3 } \right)\left( {{x_1} + \sqrt 3 } \right)…\left( {{x_5} – \sqrt 3 } \right)\left( {{x_5} + \sqrt 3 } \right) \end{array}\)
 \(\begin{array}{l} g\left( {{x_1}} \right).g\left( {{x_2}} \right)….g\left( {{x_5}} \right) = \left( {{x_1} – \sqrt 3 } \right)\left( {{x_1} + \sqrt 3 } \right)…\left( {{x_5} – \sqrt 3 } \right)\left( {{x_5} + \sqrt 3 } \right)\\ = \left( {\sqrt 3 – {x_1}} \right)…\left( {\sqrt 3 – {x_5}} \right).\left( { – \sqrt 3 – {x_1}} \right)…\left( { – \sqrt 3 – {x_5}} \right).{( – 1)^{10}}\\ = f\left( {\sqrt 3 } \right).f\left( { – \sqrt 3 } \right)\\ = – 1628 \end{array}\)